STRATEGI DIFERENSIASI PRODUK DAN JASA DI INDUSTRI DIGITAL PRINT - Made Bayu Krisnamurti; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2015)
analyse the differentiation strategy of Products and Services in the DigitalPrint Industries Denpasar. Increasing number of businesses Digital Print makes each companyrequires differentiation of products and services as their business differentiator. Increasingnumber of players and strategies tendency to slam the price makes this Industry almost cometo red ocean bussiness that would endanger the existence of the industry itself.This study analyzing qualitative data from the company of Digital Print which isconsidering quite strong, aggressive and survive in the competition. There are several playersin the industry in Denpasar where researchers perform data collection and analysis. Theselection of two company hat described in Results were based on data collectionfromsuppliersof Machinery and Raw Materials that’s conducted by researchers. Both are rated have thedifferent characteristics and both leading the industrial marketin Denpasar Digital Print withmore than sixty percent market share.In this Study the mentioned two Companies have specific characteristic to face thecompetition, survive and win the competition. One company has numbers of outlets, long outletworking hours, and price leadership. This company is still making an investment of newproduction machinestobust the image ofits business. Other companies choose to stay focusonspecific consumer segments, with a premium quality. This company is usinga good partnershipstrategy with the corpotate customer. Thi scompany continue to invest the latest productionmachines to create advantages compared to its competitors and promote quality productsandgoodservicesfor his market segments. SWOT analysisis used to analyze the DifferentiationStrategy of Products and Services in accordance with their strengths, weaknesses,Opportunityand Threats that are owned by their respective companies. Summary of Product and ServicesDifferentiation Strategy were used by the two companies later in the analysis compared withexisting theories of Differentiation Products and Services.Keywords: Digital Print, Differentiation Strategy of Products and Services.